ECSCW 2009: Proceedings of the 11th European Conference on Computer Supported Cooperative Work, 7-11 September 2009, Vienna, Austria - Wagner, Ina; Tellioglu, Hilda; Balka, Ellen; Simone, Carla; Ciolfi, Luigina (Springer London : Imprint: Springer, 2009)
This volume presents the proceedings of ECSCW'09, the 11th European Conference on Computer Supported Cooperative Work. Each conference offers an occasion to critically review our research field, which has been multidisciplinary and committed to high scientific standards, both theoretical and methodological, from its beginning. These proceedings represent discussions and contributions to ongoing challenges. One challenge comes from emerging new technologies connected to 'social computing', gaming, as well as applications supporting citizen participation in their communities. As boundaries between home and work erode with the increased movement of work into home environments, and new applications further blur the once separate conceptions of work and leisure, our intellectual community faces challenges in the ways we think about and study work. Other challenges result from transformations of the world of work itself and the role of IT in these. They have been taken up in in-depth studies of design practice, software development, and manufacturing, as well as in the growing body of research on health care contexts and applications. Finally, there is the question of what is the European perspective in our community and whether it is worthwhile to anchor our research more firmly in such a perspective. Of high relevance to our field is the strong grounding of technology development in an understanding of human activity. The nineteen full papers, four short papers and one discussion paper selected for this conference deal with and reflect on some of these challenges, thus representing the lively debate currently ongoing in our field of research.